KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN LAJANGIRU KECAMATAN UJUNG PANDANG KOTA MAKASSAR - Achmad, Deden; Tahir, Nurbiah; Arfah, Sitti Rahmawati (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThis research aims to find out the quality of public services in the Office of The Village of Tunggaliru Subdistrict Ujung Pandang Makassar City. The type of research used is qualitative research. The data sources used are primary and secondary. The number of informants is 5 people. Data collection is done using observation, interview and documentation techniques. Data analysis techniques using data reduction measures, data presentation, data verification, and using the application of triangulation data, namely source triangulation, technique and time. The results showed that the quality of public services applied in the Village Office of Tunggaliru Subdistrict of Ujung Pandang Makassar City is still less qualified when viewed from several indicators of the main dimensions in the quality of public services according to Parasuraman (2012): the only dimensions of physical appearance (tangibles) such as office facilities that are still less comfortableKeywords: Quality of Public Service, Village.